Relationship between Family Support and Family Burden in Families With Cancer: Meta-Analysis - Sang Ayu Made Adyani; Arief Wahyudi Jadmiko (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Cancer is a chronic disease caused by abnormal cell growth with special care needs that cause a burden on the family. Family support can have a significant impact on family burden. Adequate support from family members can lighten the burden on individuals or families and improve their overall well-being. This study aimed to estimate the relationship between family support on family burden in families with cancer obtained from several previous similar studies.Subjects and Method: This research was conducted using a systematic review and meta-analysis with PICO namely, Population: family with cancer; Intervention: good family support; Comparison: Lack of family support; Outcome: family burden. By searching articles in 4 databases namely PubMed, Google Scholar, Science Direct, and ProQuest published from 2014 to 2022, entering the following keywords “Family support” OR “Supportive Family” AND “Family Burden” OR “Family depresssion” AND “Chronic Disease” AND “Cancer” AND “Multivariate Analysis”. Articles were selected using PRISMA flow and data analysis using the Review Manager 5.3 application.Results: There 9 articles using the Cross-Sectional study design with a total sample of 2,832 subjects from India, Japan, USA, Swiss, Austria, Yunani, Germany, and Mexico which have been subject to systematic review and meta-analysis. The results showed that good family support are effective in decreasing family burden, and the results are statistically significant. Families with cancer who receive good family support are decrease family burden 0.57 times than families with cancer receive lack family support (aOR= 0.57; 95% CI= 0.38 to 0.85; p= 0.006).Conclusion: Good family support are effective in decreasing family burden.Keywords: family support, family burden, chronic disease, cancer.Correspondence: Sang Ayu Made Adyani. Nursing Department, Faculty of Health, Universitas Pembangunan Nasional Veteran Jakarta. Jl. RS. Fatmawati Raya, Pd. Labu, Cilandak, Depok, West Java. Email: adyani.sangayu@upnvj.ac.id. Mobile: +62 819-3206-5946.Indonesian Journal of Medicine (2023), 08(02): 169-178https://doi.org/10.26911/theijmed.2023.08.02.06